Comparative evaluation of isolation techniques and characterization of red pulp macrophages from pig splenocytes - Vu, Phu Chi; Dang, Nhat Minh; Jung, Jonghyeok; Kim, Min Hyuk; Lee, Min Guk; Shim, Joohyun; Hoang, Thi Xoan; Kim, Jae Young (Frontiers in Immunology, 2025)
IntroductionRed pulp macrophages (RPMs) play a central role in iron recycling and immune regulation within the spleen, yet optimized methods for the isolation and characterization of pig RPM remain limited.MethodsWe compared two approaches for isolating RPMs from pig splenocytes: CD163 antibody- based sorting and magnetic-activated cell sorting (MACS), which leverages the natural iron content and autofluorescence of RPMs. Isolated cells were evaluated by flow cytometry for marker expression, and functional assays were performed to assess phagocytic activity and gene expression related to iron metabolism.ResultsFlow cytometry identified an autofluorescent population, a hallmark of RMPs, within the pig splenocytes. CD163-based method enriched RPMs to 71.8% autofluorescent cells, while the MACS- based approach achieved a higher yield of 81% autofluorescent cells without using antibodies, demonstrating greater cost-effectiveness and efficiency. Marker analysis revealed high expression of CD16 and CD163, moderate expression of CD11b, and low or undetectable levels of CD14, CD32, and CD169. Functionally, isolated RPMs demonstrated robust phagocytosis of senescent red blood cells and upregulation of genes involved in heme and iron metabolism.DiscussionThese findings establish an optimized, antibody-free protocol for efficient isolation of pig RPMs. The approach provides a reliable platform for studying splenic macrophage biology, iron homeostasis, and immunological research and splenic function studies.